The superhero symbol : media, culture, and politics - Burke, Liam (Liam P.); Gordon, Ian, 1954-; Ndalianis, Angela, 1960- (Rutgers University Press, 2020)
"As a man, I'm flesh and blood, I can be ignored, I can be destroyed; but as a symbol ... as a symbol I can be incorruptible, I can be everlasting". In the 2005 reboot of the then dormant Batman film franchise, Batman Begins, Bruce Wayne articulates how the figure of the superhero can serve as a transcendent icon. It is hard to imagine a time when superheroes have been more pervasive in our culture. Today, superheroes are intellectual property jealously guarded by media conglomerates, icons co-opted by grassroots groups as a four-color rebuttal to social inequities, masks people wear to more confidently walk convention floors and city streets, and bulletproof banners that embody regional and national identities. From activism to cosplay, understanding how these different groups and interests have made use of this powerful icon is essential to unmasking the appeal of superheroes and their wider impact. To address this interest, The Superhero Symbol brings together scholars from a range of disciplines, alongside key industry figures. Collectively, these contributions provide fresh perspectives on how these costume-clad heroes have engaged with media, culture, and politics, thereby becoming the "everlasting" symbols to which a wayward Bruce Wayne once aspired"--